UJI COBA ARANG SEKAM PADI SEBAGAI MEDIA FILTRASI DALAM MENURUNKAN KADAR Fe PADA AIR SUMUR BOR DI ASRAMA JURUSAN KESEHATAN LINGKUNGAN MANADO - Jasman Jasman (Jurnal Kesehatan Lingkungan, 2011)
Water is a chemical compound that is essential for the life of mankind and other living being sand their function as life will not be replaced by other compounds. Filtration is a process of water treatment by means of raw water flowing through a filter with media from granular materials with a certain grain diameter and arranged with a certain thickness. This type of research is experimental, with the aim to determine whether there is decreased levels of Febyrice huskcharcoal filtration at the water wells drilled in Environmental Health Dormitory Manado. Filtration arrangement made with gravel, palm fiber and rice huskcharcoal. Data obtained from the research results processed by using statistical test student "t" test. The conclusion that the pilot rice husk charcoal as media filtration to reduce levels of iron in well water drill that most effectively reduce levels of Fe as follows : 0.0085 mg/l (first sample) and 0, 0001mg/l (second sample). Filtration mediausing rice huskcharcoal presumably to the public to be reducing levels of Fe.